New Efficient Synthesis of 2-Thioxo-2,3-dihydropyrimidin-4(1H)-ones from Baylis–Hillman Adducts - Chen, Xiuhua; Zhong, Ying; Zhao, Zhigang; Huang, Gang (Synthesis, 2017)
Azides obtained from Baylis–Hillman adducts were treated with triphenylphosphine to give the corresponding iminophosphoranes, which reacted with carbon disulfide at 40 °C to produce isothiocyanates. The reaction of these isothiocyanates with primary amines provided thiourea intermediates, which in the presence of potassium carbonate or sodium methoxide were converted into 2-thioxo-2,3-dihydropyrimidin-4(1H)-ones in good yields.
Keywords: Baylis–Hillman adducts; iminophosphoranes; isothiocyanates; primary amines; aza-Wittig reaction; 2-thioxo-2,3-dihydropyrimidin-4(1H)-ones